MAPPING OF FIRE EXTINGUISHER: A CASE STUDY IN ISLAMIC BOARDING SCHOOL GONTOR 2 PONOROGO - Diannita, Rindang; Mayang Phuspa, Sisca; Ma'rifah, Siti (Universitas Darussalam Gontor, 2025)
Fire cases are one of the disasters that are increasing every year, one of the causes is the inadequate fire protection system and skills in using fire extinguishers. Gontor 2 Islamic Boarding School Ponorogo is a place that has 24-hour student activities with large electricity needs, continuous kitchen activities to provide dining facilities for students, as well as unsafe behavior and flammable materials that can be opportunities for fires. This study is to map the active fire protection system in the form of fire extinguishers and to map safety signs in the form of gathering points and evacuation routes. Method: This study is an analytical qualitative study, with a descriptive method supported by interview data and field surveys. Primary data comes from the results of field surveys and observations of active fire protection systems and safety signs using a checklist form that refers to the results of interviews with managers. The study found that it is still necessary to increase the distribution capacity of Fire Extinguishers owned, mapping safety signs in the form of evaluation routes and gathering points, and increasing the procurement of fire fighting facilities and infrastructure. Based on the mapping results, areas that have the potential for fire are the kitchen, cafeteria, residential areas of the caretakers of the boarding school, high-rise buildings, and there is still a need to increase the number of Fire Extinguishers by 30 units, evacuation routes by 22 units, gathering points by 2 units, and efforts to maintain fire protection equipment.